Morphological analysis of Polyethersulfone/polyvinyl Acetate blend membrane synthesized at various polymer concentrations - Hadi, S.H.A.A. (Institute of Physics Publishing, 2016)
This paper reports the effect of varying polymer concentration i.e. solvent/polymer ratio on the morphology and gas transport behaviour of polyethersulfone/polyvinyl acetate blend membrane. The solvent used was dimethylformamide, while the manipulated variable was polymer concentration. The concentrations were varied from 75-90 weight solvent. A homogeneous surface with dense cross-section structure membranes were successfully developed as deduced from FESEM images. The permeability of CO2 and CH4 gases increased with increasing polymer concentration and an improved CO2/CH4 selectivity was observed. These observation made from the characterization justified the applicability of the blend to be synthesized as membrane for gas separation. Â© Published under licence by IOP Publishing Ltd.